The amazing bond among wine consumption, health and hedonistic well-being. Issue 8 (28th October 2019) - Fiore, Mariantonietta; Alaimo, Leonardo Salvatore; Chkhartishvil, Nino
Abstract : Purpose: Wine, fruits, vegetables and whole grains are the main products of a healthy diet. The purpose of this paper is to scrutinize the existence of an interesting and evocative bond among moderate intake of wine, health and well-being. Design/methodology/approach: By means of a fuzzy cluster analysis, the authors try to investigate the existence of groups of regions similar in wine consumption, subjective well-being, health and social relations. The latter are expressed through composite indicators, built and developed by Istat within the Italy ESW project's activities (equitable and sustainable well-being). The analysis also investigates how this link has evolved over time. Data are related to refer to the situations in 2010 and 2017 in 21 regions of Italy. Findings: Results obtained in 2010 seem to confirm the hypothesis of the existence of a link among moderate wine consumption, hedonism well-being and health, and in addition, findings highlight the so-called North‒South gap, that is the strong differences and economic issues among the different areas of the country. Then, outcomes obtained for 2017 appear in line with 2010 results. Originality/value: Several authors from medicine, economics and chemistry domain strongly suggest and demonstrate that regular and moderate intake of wine reduces the incidence of heart disease, diabetes mellitus and hormonal problems, and correlatively increases longevity. In this work, the authors develop further research step including the aspects related to personal well-being and social relations under the umbrella of a hedonism approach. Finally, results highlight the existence of an amazing tie among moderate intake of wine consumption, well-being and health.